KOMPETISI POLITIK, PENDAPATAN ASLI DAERAH DAN OPINI AUDIT TERHADAP IMPLEMENTASI E-GOVERNMENT - Rinda Dwi Utami; Dini Wahjoe Hapsari; Dewa P. K Mahardika (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2019)
This study analyzes the influence of political competition, regional original income (PAD) and audit opinion on the implementation of e-government. Political competition is measured by the number of elected provincial DPRD members per period. Regional original income is measured by the acquisition of annual regional original revenues and audit opinion is measured by the results of the BPK’s examination of the annual regional financial statements. This research uses quantitative methods and includes descriptive verification categories. The sample was selected using the purposive sampling method, namely the province in Indonesia and contained in the Indonesian e-government Rating (PeGI) in 2012-2015. Hypothesis testing uses panel data statistical methods. The results of the study showed that local original income partially has significant effect on the implementation of e-government. Meanwhile, political competition and audit opinion do not indicate a significant influence on the implementation of e-government.